2017
DOI: 10.1007/978-3-319-52875-5_10
|View full text |Cite
|
Sign up to set email alerts
|

What do job adverts tell Higher Education about the ‘shape’ of Biomedical Engineering Graduates?

Abstract: Abstract-Higher Education Institutions are required, at least in some Countries, to design their curricula taking into account the needs of relevant industry. Use of Industrial Advisory Committees is a common way of demonstrating this input. This paper explores an additional window to industry needs through the textual analysis of job advertisements. 36 internet published adverts using the "Biomedical Engineering" search phrase were downloaded and textually analysed to identify the mentioned technical skills, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The soft skills that employers emphasize most are communication skills, teamwork skills and analytical skills. This highly matches the results of other research that adopt a similar job ads analysis method but for different engineering positions, such as requirement engineers [14], software engineers [45], civil engineers [16] and biomedical engineers [15]. This is because the soft skills are not subject-specific, and the requirement is similar due to the jobs' engineering nature.…”
Section: Soft Skillssupporting
confidence: 85%
See 1 more Smart Citation
“…The soft skills that employers emphasize most are communication skills, teamwork skills and analytical skills. This highly matches the results of other research that adopt a similar job ads analysis method but for different engineering positions, such as requirement engineers [14], software engineers [45], civil engineers [16] and biomedical engineers [15]. This is because the soft skills are not subject-specific, and the requirement is similar due to the jobs' engineering nature.…”
Section: Soft Skillssupporting
confidence: 85%
“…Apart from RE jobs, job ads analysis has been applied to other engineering disciplines. Aiming at shaping the biomedical engineering graduates in the UK with curriculums that represent the needs of the industry, instead of using an industry advisory committee for high education curriculum design, [15] explored an alternative approach to see the industry needs through the job ads analysis, using qualitative analysis software. Results reveal the relevant technical skills hierarchy and rated importance of generic skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The bulk of the literature on necessary skills for engineering jobs focuses on professional, rather than technical skills: a mapping review of empirical research studies on practicing engineers found that of the 45 papers that discussed the competencies and attributes needed or used by practicing engineers, only 5 investigated specific technical competencies (Mazzurco et al, 2021). Studies of the technical skills needed for engineering jobs have primarily been conducted outside of the United States, including biomedical engineers in the United Kingdom (Ward et al, 2017), civil engineers in Turkey (Gerek & Efeoglu, 2015), and software engineers in Jordan (Jebreen & Nabot, 2021). In the United States, PhD‐level engineers in industry report that their work included research‐related tasks such as creating new tools, conducting simulations, developing new techniques, running experiments, and testing hypotheses (Ahn et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surveys are carried out periodically by the UK Government, the latest being 2019 [1]; by Professional Bodies, the most recent IET survey was reported in 2019 [2]; by consultancies, such as the McKinsey 2020 report [3] and by funded projects specifically designed to explore sector skills gaps, an example being the EIE-Surveyor project [4]. Job advert analysis gives a restricted but different insight into skills required by recruiting companies [5], [6] while individual, larger sized recruiter companies also list skills required for a range of careers and specific vacancies, examples being indeed [7] and target jobs [8].…”
Section: Introductionmentioning
confidence: 99%